Classroom Oral Presentation: Students’ Challenges and How They Cope - Arifah Mardiningrum; Dea Rizky Ramadhani (Makassar State University, 2022)
Abstract. Classroom oral presentation is one of the techniques that has been used in any language classroom to provide an opportunity for language practice. This research investigates EFL students' challenges in classroom oral presentation and their strategies to face the challenges. The presentations covered group and individual presentations. Using a qualitative research approach and a descriptive design, authors collected data through in-dept interviews. Participants were four students of the English department of one private university in Yogyakarta, Indonesia, who had multiple experiences performing oral presentations in the classrooms that they had been attending for at least three years. The study found nervousness, group dynamics, audience, missing points, challenging content, language boundaries, and high self-expectation as the challenges the participants faced in classroom oral presentations. In addition, the study also discovered that strategies used to overcome the challenges were self-assurance, better preparation, peer discussions, directed eye contact, direct communication, backups, self-isolation, and presentation aids use. The implication is that in EFL classroom contexts, all factors surrounding the students might play a part in the way students view their experience and their success in an oral presentations. It also implied that eventually, students will have the ability to utilize the resources around them to solve their issues in an oral presentation. This gives an insight to how teachers can provide the environment that enables students to independently solve their problems. Keywords: Classroom Oral Presentation, Challenges, Strategies To Face The Challenges, CBI, CLT